Fetuin-A, glycemic status, and risk of cardiovascular disease: The Multi-Ethnic Study of Atherosclerosis. (May 2016) - Aroner, Sarah A.; St-Jules, David E.; Mukamal, Kenneth J.; Katz, Ronit; Shlipak, Michael G.; Criqui, Michael H.; Kestenbaum, Bryan; Siscovick, David S.; de Boer, Ian H.; Jenny, Nancy S.; Budoff, Matthew J.; Ix, Joachim H.; et al.
Abstract: Aims: Fetuin-A is a hepatic secretory protein that both promotes insulin resistance and inhibits arterial calcification. Previous studies have suggested that the association of fetuin-A with incident cardiovascular disease (CVD) might be modified by glycemic status. Methods and results: We conducted a case-cohort study of fetuin-A and incident non-fatal CVD nested in the Multi-Ethnic Study of Atherosclerosis with follow-up from 2000 to 2007. Fetuin-A concentrations were measured from baseline serum samples among 2505 randomly selected subcohort members and 142 incident cases. In weighted multivariable Cox regression models, no association was observed between fetuin-A and incident CVD in the total study population (HR per SD = 1.01; 95% CI: 0.84, 1.23). Although associations with CVD events were not statistically significant within categories of glycemic status, our results tended to support the interaction with glycemic status observed in other studies, with a positive trend restricted to participants with impaired fasting glucose or diabetes (HR per SD = 1.20; 95% CI: 0.89, 1.63) and an inverse trend among normoglycemic individuals (HR = 0.89; 95% CI: 0.69- 1.13) (p-interaction = 0.04). In addition, we observed significant interaction between fasting glucose and fetuin-A when both were treated continuously in the subset of participants not using diabetes medication (p-interaction = 0.006). Conclusion: Our results suggest that fetuin-A is not associated with an overall risk of CVD, but support prior evidence indicating that the association might be modified by glycemic status. Highlights: Fetuin-A and risk of CVD was prospectively examined in a multi-ethnic population. No overall association between serum fetuin-A and CVD events was found. The association of fetuin-A with risk of CVD was found to depend on glycemic status. Fetuin-A tended to be inversely associated with CVD events in normoglycemic persons. Fetuin-A was directly associated in those with impaired fasting glucose or diabetes.